Enjoying : Red Dot design yearbook 2016/2017 - Zec, Peter, 1956- (Essen : Red Dot, 2016)
"Enjoying" is the new fourth volume of the Red Dog Design Yearbook 2016/2017 and visualises products from areas such as bathrooms and spas, vehicles, consumer electronics and camera, as well as communication. Additionally, the design team of the year, as well as designer and jury portraits will be shown.
Includes index.
Text in English and German.
Keywords: Industrial design -- Periodicals